‘In Google we trust’? The Internet giant as a subject of contention and appropriation for the Russian state and civil society - Bronnikova, Olga; Zaytseva, Anna (First Monday, 2021)
This article explores an apparent paradox related to the use of Google services in Russia: several NGOs based in the country consider the Internet giant as a protector of civil liberties. The highly polarized Russian political context, in which local technological companies are increasingly controlled by the State, explains the widespread uses of Google services in daily practices of NGOs. We show how their risk model is focused on the threat emanating from the State, seen as more important than risks emanating from global private companies. In this context, “big tech” solutions are preferred to open source software as they are valued for their usability. Internet giants, such as Google, are understood by civil society actors as powerful allies in this internal confrontation, as their dominant economic role is seen as a guarantee that they will not yield to pressure from authorities. Finally, we will see how, in parallel, self-regulatory virtues of the competitive global IT market, and the strength of global public opinion, are supposed to “naturally” force these companies to comply with ethical standards in data use.